Hubungan Intake Cairan dengan Tekanan Darah pada Pasien Gagal Ginjal Kronik (GGK) yang Menjalani Hemodialisa: Relationship between Fluid Intake and Blood Pressure in Patients Chronic Kidney Failure (CKD) Patients Undergoing Hemodialysis - Fitri Mailani; Ginza Johanda (Fakultas Keperawatan Universitas Andalas, 2018)
Excessive fluid intake in patients with chronic kidney failure will cause complications that lead to death. This study aims to determine the relationship between fluid intake and blood pressure in patients with chronic renal failure undergoing hemodialysis at Rs. Tk III Dr. Reksodiwiryo Padang. This type of research was descriptive correlation, with a sample of 49 respondents taken by consecutive sampling technique. Data collection and research was carried out on March 15 to July 4, 2018. The method of collecting data with observation sheets and questionnaires. Univariate analysis was carried out by presenting data in the form of the mean, standard deviation, minimum, and maximum while bivariate analysis used a correlation test with Rank Spearman. The results of the univariate study of Sistole Blood Pressure from 49 patients obtained a minimum value of 0 mmHg, and the maximum value was 60 mmHg, the standard deviation was 12.69, the mean value was 16.33 mmHg. Whereas in the Diastole Blood Pressure the minimum value is -20mmHg (reduced by 20mmHg), and the maximum value is 30, the mean value is 9.18 mmHg. The fluid intake minimum value is 825.7 ml, maximum is 2216.7 ml, and mean is 882 ml. Bivariate results showed that there was a relationship between fluid intake and systolic blood pressure (p = 0.032) and diastolic blood pressure (p = 0, 013). It is hoped that collaboration between patients, families and nurses in monitoring the patient's fluid intake to prevent complications due to fluid buildup.